The Attitude of Campus Da’Wah Institution Administrtator (LDK) Toward Pancasila - Rena Kinnara Arlotas (Jurnal Kewarganegaraan, 2020)
Abstract Campus Da’wah Institution (LDK) is one of Student Activity Units (UKM) which is internal aimed to facilitate Muslim student in terms of self-development as well as to improve Islamic insight. Recently, the are quite a lot of issue stating that LDK is against Pancasila, therefore it is considered as a threat to the national integrity of Republic of Indonesia. However, throughout Indonesian Silaturrohim Forum of Campus Da’wah Institution (FSLDK), LDK denied the accusation. The purpose of this research is to reveal the actual attitude of LDK administrator toward Pancasila as to whether it is against or the otherwise. This is a quantitative descriptive research. Data were collected through scale which arranged based on the attitude component proposed by Ronto (2012). The research population consists of 29 LDK located in West Sumatera in which 16 LDK as the research samples consist of 121 administrators who are the subject of the research. The research result revealed that 95 persons or 47.26% are strongly agree toward Pancasila, and 106 persons or 52.7 % agree toward Pancasila. None of them disagree or strongly disagree. This finding signified that the attitude of LDK administrator toward Pancasila is positive which is agree and strongly agree. Keywords: Attitude, LDK Administrator, Pancasila